Relationships among foreign language anxiety, academic self-efficacy beliefs and metacognitive awareness: A structural equation modelling - Tuncer, Murat; Doğan, Yunus (My University, 2016)
The present research attempted to investigae the relationships among foreign language classroom anxiety, academic self-efficacy beliefs and metacognitive awareness of Turkish university students studying English. The population included the students at the University of Fırat who were already registered to study at different engineering departments, and had compulsory English prep-class education. The sample consisted of 271 students who wanted to take part in the study. For data collection, the Foreign Language Classroom Anxiety Questionnaire developed by Horwitz et al (1986), the Academic Self-efficacy Questionnaire developed by Owen and Froman (1988) and the Metacognitive Awareness Inventory developed by Schraw and Dennison (1994) were used. The analyses of the study were carried out by using structural equation modelling. As a result, it was found that academic self-efficacy predicted foreign language classroom anxiety significantly in a positive way; academic self-efficacy predicted metacognitive awareness significantly in a negative way, and foreign language classroom anxiety predicted metacognitive awareness significantly in a positive way.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Foreign language anxiety; Metacognitive awareness; Structural equation modelling